Comment on "The two-step nucleation of G-phase in ferrite", the authors: Y. Matsukawa et al. Acta Mater 2016; 116:104–133. (1st April 2019) - King, D.J.M.; Wenman, M.R.
Abstract: Recently, Matsukawa et al. [1] published a paper investigating the nucleation and growth of Mn6 Ni16 Si7 G-phase precipitates in duplex stainless steel using experimental and theoretical techniques. The G-phase cubic unit cells simulated by the authors for the theoretical analysis are non-physical, with lattice parameters of ≤0.550 nm, leading to a partially erroneous conclusion regarding the structure of the observed precipitates. In this comment we use density functional theory results from our previous study of the G-phase [2] to offer an alternative explanation to the experimental observations made by Matsukawa et al., viz, the Mn-Ni-Si precipitate is in an intermediate P1 structure, resulting from an energy minimum, in the transformation from BCC packing to G-phase.